Temperature-dependent toxicity and mechanisms of florfenicol on the embryonic development of marine medaka (Oryzias melastigma) - Xingying Guo; Xu Gong; Jinhui Wang; Tan-Duc Nguyen; Syed Shabi Ul Hassan Kazmi; Jiezhang Mo; Feng Hua; Wenhua Liu; Zhen Wang (Ecotoxicology and Environmental Safety)
The extensive use of antibiotics and their persistence in the environment have seriously threatened marine ecosystems in recent years. The frequent occurrence of extreme weather due to climate change has also increased the uncertainty of effective toxicity identification and risk assessment of the chemicals of concern. This study aimed to investigate the toxic effects and potential mechanisms of florfenicol (0.5, 10, 100, 500 and 1000 μg/L) on the embryonic development of marine medaka (Oryzias melastigma) through 21-d experiment under three temperature exposure scenarios (20, 25, and 30 °C). Considering embryo development, the highest level of florfenicol at 1000 μg/L decreased the hatching success at 25 °C, whereas the total inhibition of hatching was observed at 20 °C regardless of florfenicol concentrations of concern. The ATP content was inhibited by the highest florfenicol dose at 20 °C, while stimulated ATP content at 20 °C and 30 °C, compared to 25 °C. Fluctuation of temperatures, especially at 20 ℃, induced oxidative stresses, including increased MDA contents and decreased CYP450 and HSP90 contents. For inflammatory response-related genes (nf-κb, nlrx1, pycard, caspase 1, and il-1β), an increase of florfenicol dose led to gene upregulation at 25 °C. Conversely, gene upregulation was also observed for all treatments at 30 °C, while predominantly downregulation was observed for all treatments at 20 °C. For genes related to DNA damage and apoptosis (pi3k, akt, foxo1, tp53, bcl-2, bax, apaf-1, caspase 9, and 3), alterations in gene expression were evident for all florfenicol treatments at both 20 °C and 30 °C. Therefore, this study suggests that the combined effects of florfenicol and temperature may disrupt the normal function of mitochondria, impacting ATP production, thereby inducing oxidative stress, inflammatory response, DNA damage, and apoptosis, ultimately resulting in decreased hatching rates and increased mortality. Furthermore, the key findings of this study reveal the complex interactions between florfenicol and temperature and emphasize the need to consider temperature when identifying toxicity and mechanisms, as well as the ecological risk assessment of florfenicol in marine environments.